Sindrom Balint - Hanna Karmila; Leonirma Tengguna (Cermin Dunia Kedokteran, 2018)
Sindrom Balint disebabkan lesi bilateral pada perbatasan lobus parieto-oksipital dengan trias gejala utama simultanagnosia, ataksia optik, dan apraksia okular. Berbagai faktor penyebab adalah stroke, trauma kepala, tumor otak. Sindrom Balint terkadang salah didiagnosis sebagai kelainan visus; diperlukan pendekatan teliti agar penatalaksanaan tepat.Balint syndrome is a disorder of simultanagnosia, optic ataxia, and ocular apraxia that typically results from bilateral parieto-occipital lesions. Many causal factors are stroke, traumatic brain injury, tumor, etc. Balint syndrome sometimes is misdiagnosed as disorder of visual acuity; detailed approach is necessary to identify the etiology and provide the best treatment.